Evanescent Wave Absorption Sensor Based Tapered Plastic Optical Fiber Coated with Monolayer Graphene for Ethanol Molecules Detection - Jiang, Shouzhen; Qiu, Hengwei; Gao, Saisai; Chen, Peixi; Li, Zhen; Yu, Kaiyang; Yue, Weiwei; Yang, Cheng; Huo, Yanyan; Wang, Shuyun (Chinese journal of chemistry, 2016)
An evanescent wave absorption （EWA） sensor based tapered plastic optical fiber （TPOF） coated with monolayer graphene film for ethanol molecules detection is demonstrated in this study. The continuous and monolayer graphene films were grown on a Cu foil by using chemical vapor deposition （CVD） technology. Polymethyl methacrylate （PMMA） was used as the carrier to support the transfer of graphene from Cu foil to the skinless tapered optical fiber core. The accuracy of the TPOF sensor with graphene （G-TPOF sensor） is much higher than that without gra- phene （TPOF sensor）, which can be attributed to the molecules enriched on the surface of graphene. The absorbance （A） and the concentrations of ethanol solution show an excellent proportional relationship in a range of 0--100%. The dynamic response of the G-TPOF sensor has shown strong reversibility, repeatability and stability at room temperature. The response time and recovery time of the G-TPOF sensor for different concentrations are all less than 30 s. Beyond that, we selected the Chinese liquor as the analyte, and the results are consistent with the concen- tration-list obtained in the experiment.